If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X/7-4=-X+3
We move all terms to the left:
X/7-4-(-X+3)=0
We add all the numbers together, and all the variables
X/7-(-1X+3)-4=0
We get rid of parentheses
X/7+1X-3-4=0
We multiply all the terms by the denominator
X+1X*7-3*7-4*7=0
We add all the numbers together, and all the variables
X+1X*7-49=0
Wy multiply elements
X+7X-49=0
We add all the numbers together, and all the variables
8X-49=0
We move all terms containing X to the left, all other terms to the right
8X=49
X=49/8
X=6+1/8
| X+-4+x=12 | | 92=8y-4y | | x*x−20x+100=0 | | -2/5x-6=-48/5 | | 2/9x+x=5/6x-1/3 | | 14-4n=5 | | 1/3x+2x-1=x+3 | | 8×4×k+9×5=(36-4)k-(2×5) | | 2-x-7=35x+2 | | x+4÷-2=3x+1÷3 | | -6=-2r+8r | | 31.20=6g+3.84 | | 4a+1=7a+4 | | 5(8x-1)+2x=-4 | | -7n-4=-4n-(n-8) | | -6+6n=n+8n | | 3n-4n=6 | | -3x+2(x+5)=6 | | 20x/6=5x/3 | | 20w-9w=4(15-w) | | 24x-18+8x=14 | | 4m-7m=12 | | 4x-6x/2=6-2x | | 3+2z+17z=79 | | -6x-3x=0 | | -7b-2b=18 | | -5p-8p=39 | | 3(8x-6)+8x=14 | | 6+2x+9=x+11 | | 7+½(6x+4)=-2x+4 | | 5(x-2)-3=3(x+1)-9x | | 3x-6(x+4)=-9 |